Zero Trust Architecture and Business Risk Alignment: Comprehensive Governance Framework, Implementation Methodologies, and Future Security Trends for Enterprise Environments - Olomola, Abiola (International Journal of Scientific Research and Management (IJSRM), 2024)
Zero Trust Architecture (ZTA) represents a transformative approach to cybersecurity, shifting focus from traditional perimeter defenses to continuous verification and strict access controls across users, devices, and applications in diverse environments. This work explores the theoretical foun- dations, core principles, and evolving models of Zero Trust, emphasizing alignment with business risk management and regulatory compliance. It examines architectural frameworks and implemen- tation methodologies tailored for on-premise, cloud-native, hybrid, and multi-cloud deployments, highlighting challenges and best practices for integration. Key components such as identity and access management, network segmentation, policy enforcement, and multi-factor authentication are analyzed alongside the role of advanced technologies including Security Information and Event Management (SIEM), behavioral analytics, machine learning, and automation. The discussion extends to governance structures, stakeholder engagement, and metrics for measuring success, underscoring the necessity of continuous monitoring, incident response, and adaptive defenses in dynamic threat landscapes. Emerging trends in AI, Internet of Things (IoT), Operational Tech- nology (OT), and Secure Access Service Edge (SASE) integration are also addressed, illustrating the critical role of Zero Trust in supporting digital transformation and resilient enterprise security in complex, distributed infrastructures.